Peripheral cementifying fibroma: a clinical diagnostic dilemma - Choubey, Shikha (BMJ Publishing Group, 2013)
The peripheral ossifying fibroma (POF) is a reactive gingival overgrowth occurring frequently in the anterior maxilla. It originates in the cells of the periodontal ligament and is more common in children and young adults. In the current article a case of gingival over growth, which was thought to be puberty-induced gingivitis was seen in the lower anterior maxillary gingiva. Histology of the excised tissue showed cellular, fibrous connective tissue stroma with calcified osseous calcifications indicative of POF. The definitive diagnosis is established only by histological examination, which revealed the presence of highly cellular connective tissue with focal calcifications. Surgery is the treatment of choice, though the recurrence rate can reach 20% in case of POF. After histological confirmation the recall and clinical evaluation protocol of POF varies due to its increased recurrence rate, which the general dentist should be aware of.